Modeling quality and prestige in applied linguistics journals: A bibliometric and synthetic analysis - Xu, Yiran; Zhuang, Jingyuan; Blair, Ryan; Kim, Amy I.; Li, Fei; Hernández, Rachel Thorson; Plonsky, Luke (Studies in Second Language Learning and Teaching, 2023)
The importance of academic journals in second language (L2) research is evident on at least two levels. Journals are, first of all, central to the process of disseminating scientific findings. Journals are also critical on a professional level as most L2 researchers must publish articles to advance their careers. However, not all journals are perceived as equal; some may be considered more prestigious or of higher quality and may, therefore, achieve a greater impact on the field. It is therefore necessary that we understand the identity and quality of L2 research journals, yet very little research (e.g., Egbert, 2007; VanPatten & Williams, 2002) has considered these issues to date. The current study sought to explore L2 journal identity and quality, and the relationship between these constructs. In order to do so, a database was compiled based on three different types of sources: (1) a questionnaire eliciting L2 researchers’ perceptions of the quality and prestige of 27 journals that publish L2 research (N = 327); (2) manual coding of different types of articles (e.g., empirical studies, review papers), data (quantitative, qualitative, mixed), research settings, and authorship patterns (K = 2,024) using the same 27 journals; and (3) bibliometric and submission data such as impact factors, citation counts, and acceptance rates. Descriptive statistics were applied to explore overall quality and prestige ratings as well as publication trends found in each journal. The relationships between those patterns and subjective ratings were also examined. In addition, regression models were built to determine the extent to which perceptions of journal quality and prestige could be explained as a function of journal and article features. We discuss the findings of the study in terms of on-going debates concerning publication practices, study quality, impact factors, journal selection, and the “journal culture” in applied linguistics.